MODERASI BERAGAMA DALAM KEPEMIMPINAN ALI BIN ABI THALIB PERSPEKTIF HADITS TEMATIK - Farhan Shirath; Zaimudin Zaimudin; Iin Kandedes (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2026)
Religious moderation is an important concept in Islam that emphasizes justice, balance, tolerance, and the avoidance of extreme behavior in religious practice. This study aims to analyze the concept of religious moderation in the leadership of Ali ibn Abi Talib from the perspective of thematic hadith studies. This research employs a qualitative method using a library research approach and thematic hadith (maudhu’i) analysis. Primary data were obtained from classical hadith literature, while secondary data were collected from books, journals, and other scholarly works related to religious moderation and Islamic leadership. The findings reveal that the values of religious moderation in the Prophet Muhammad’s traditions include justice, balance, tolerance, anti-extremism, deliberation, and compassion. These values were clearly reflected in the leadership of Ali ibn Abi Talib through his fair law enforcement, tolerance toward non-Muslims, dialogical approach in resolving conflicts, rejection of extremism, application of deliberation in governance, and simple as well as humanistic lifestyle. The leadership of Ali ibn Abi Talib demonstrates that religious moderation is not merely a conceptual discourse, but can also be implemented in social and political practices. This study is expected to contribute to the development of hadith studies, Islamic leadership studies, and the strengthening of religious moderation in contemporary Indonesia.